Simulation study of kenaf dust dispersal behaviour in 20 l spherical chamber - Nurulain, Masrom (2025)
This study investigates the dispersion behaviour of kenaf dust in a 20 L Spherical Chamber, simulating silo-like conditions to address the risks of industrial dust explosions. Combustible organic material kenaf dust presents serious risks during industrial processing, particularly in enclosed spaces. The study intends to examine important dispersion metrics at different dust concentrations (250 g/m3, 500 g/m3, 750 g/m3 and 1000 g/m3), such as particle tracks, velocity, static pressure and Turbulence Kinetic Energy (TKE). The findings revealed that increased dust levels aided in the growth of agitations, pressure gradients, and interaction of particles with one another, creating an environment that was favourable for ignition and fully-fledged explosion events. It is worth noting that at 1000 g/m³ concentration of dust, turbulence build-up and pressure zones was at its highest which signifies a steep level for the potential explosion risk. The study depicted dispersion dynamics using Computational Fluid Dynamics (CFD) simulations and found that increased dust concentrations greatly increase pressure gradients and turbulence, which raises the risk of explosive situations. In order to prevent industrial explosions, the results highlight the significance of keeping kenaf dust concentration below critical levels and putting in place efficient monitoring and safety procedures. In the kenaf processing sector, our research supports sustainable practices, encourages regulatory compliance and improves industrial safety protocols.